Kajian Kenyamanan Termal Ruang Kuliah Pada Gedung Sekolah C Lantai 2 Politeknik Negeri Semarang - Demi Tria Istiningrum; Rr leidy Arumintia; Muhamad Mukhlisin; Mochammad Tri Rochadi (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2017)
In carrying out the activity, people are generally want a comfortable condition. One of the physical environmental factors that affect the level of comfort when working is thermal comfort. Thermal comfort is the feeling that someone is comfortable withthe condition of the environment temperature, which is described as a condition where a person does not feel too hot or too cold in specific environments. Things that influence the thermal comfort is air temperature, humidity, wind speed, insulant clothing value and rate of metabolic. The study was conducted in lecture room State Polytechnic of Semarang, 4 rooms on the 2nd floor have been selected as the object in this study because those rooms are located at the east and the west of building and still using natural ventilation, those rooms are SC II-01, SC II-02, SC II-09 and SC II-10. This study was conducted to determine how the level of thermal comfort in the classroom. The method used in this research is PMV (Predicted Mean Vote) and PPD (Predicted Percentage of Dissatisfied). PMV is used to determine the comfort level of student as users of the room, while the PPD is used to determine the level of student dissatisfaction as users of the room. From the results obtained in mind that the three classes in he category of heat that is SC II-01, SC II-02 and SC II-09. While another class, namely SC II-10 into the warm category.Kata kunci : PMV, PPD, Thermal Comfort, Lecture Room, Classroom